Workshop Pengelolaan Arsip Berbasis Elektronik Di Lembaga Pendidikan Non Formal - Hery Muljono; Somariah Fitriani; Fetrimen (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
Files management is a management process of aids in the recovery of archives based on applicable archival rules. Files management is a very important part in an organization or educational institution. Archives in an organization, especially in non-formal education are dynamic. It is said to be dynamic, because archives will continue to grow both in terms of number and type, in line with the development of these non-formal educational institutions. For example, the development of the number, origin, academic and non-academic achievements as well as the level of students will develop in line with the development of student specialization and registration. The electronic-based archive management workshop activities, in principle, are carried out in three stages, namely: the initial stage, the core stage and the final stage. The initial stage, as a beginner stage where the assessment of the material needed by community service participants, is in the form of delivering material about the concept of excellent service. Core stage, delivery of core material and best practice, the third stage, namely the final stage is the conclusion and evaluation of the importance of archive management in a non-formal educational institution